PARLIAMENTARY REWARDS AND THE EVOLUTION OF THE PATENT SYSTEM. (27th August 2015) - Burrell, Robert; Kelly, Catherine
Abstract: This article examines the impact on the patent system of rewards for innovation across the eighteenth and early nineteenth centuries. During this period, Parliament would regularly grant rewards to inventors, with many of these rewards being set out in legislation. This legislation provided Parliament with the opportunity to promote a model of state support for inventors: a model that made public disclosure of the invention a precondition for assistance. This had important implications for patent law, in particular, in helping to develop the role of the patent specification and the doctrine of sufficiency of disclosure. In this way, the reward system helped establish the framework under which the state would provide support for inventors. Simultaneously, however, the reward system created a space in which inventors would have to do more than meet the minimum requirement of public disclosure. Rewards allowed the state to distinguish between different classes of inventor and to make special provision for particularly worthy individuals. In this way, the reward system recognised the contribution of the "heroic inventor", whilst leaving the core of the patent system undisturbed.